유기농 쌀 생산을 위한 벼 포트육묘 이앙재배의 생육특성 - 권영립; Young Rip Kwon; 최인영; In Young Choi; 문영훈; Young Hun Moon; 서경원; Kyoung Won Seo; Praveen Kumar Sharma; 김대향; Dae Hyang Kim (Hanguk hwangyeong nonghak hoeji, 2011)
BACKGROUND: The present study was conducted to find out the suitable method for organic rice production on the basis of different seedling raising methods at nine eco-friendly agricultural units of Samgi, Mangsung, Iksan and Sungsan, Gusan of Jeollabuk-do, during 2009-10. METHODS AND RESULTS: On the basis of yield and physiological parameters, pot seeding method was found to be superior to drill seeding and broadcast seeding methods. The number of panicle, grain, the precent of ripened grains, and the 1,000 grain weight, were better in pot seeding method. Maximum yield and other attributes were recorded in rice, cultivated with seedlings raised by pot and broadcast seeding method. Number of panicle/hill and grain/panicle was 10.4% and 35.1% higher than the broadcast seeding method, respectively. Yield also showed 8.8% increase in pot seeding method as compare to broadcast seeding method. Higher grain yield was obtained when 56 hills/3.3㎡ of rice seedlings were used as compare to 50 hills/3.3㎡ raised by pot seeding method and 70 hills/3.3㎡ of broadcast seeding method. Lodging was minimum in seedlings raised with pot seeding method as thickness of third internode was more (9.0%) than the seedlings, raised with broadcast seeding method. Root length and dry weight also showed similar tendency i.e. 13.8% and 25.3% higher, respectively. CONCLUSION(s): Quality and grade of rice, cultivated with pot seeding method was better than broadcast seeding method. Head rice was 4.4% higher; and protein content and broken rice grown by pot seeding method were 0.4% and 1.8% lower than broadcast seeding method, respectively.